Kondisi Psikologis Masyarakat pada Puisi “Al-Kūlīra” Karya Nāzik Al-Malāikah dan “Lockdown” Karya Simon Armitage - Maulana, Gilang Inggit; Tasnimah, Tatik Mariyatut; Wahyudi, Jarot (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
The psychological condition of each country experiencing an epidemic in every era is certainly different. This paper describes the psychological condition in the poem "al-Kūlīra" by Nāzik al-Malāikah and the poem "Lockdown" by Simon Armitage. Both poems depict the pandemic situation in two different countries. The poem "al-Kūlīra" portrays the Cholera outbreak in Egypt, while the poem "Lockdown" is based on the Corona pandemic. The psychological theory used is Ary Ginanjar's emotional spiritual quotient. The study begins by analyzing each psychological dimension of the two poems and then comparing them. The purpose of this study is to determine and compare the psychological condition in the form of emotional spiritual quotient (ESQ) in communities affected by the corona and cholera pandemics. The methods used are descriptive, comparative, and qualitative, with a psychological approach. The data presented include every word, phrase, clause, and sentence that contains psychological elements from the poems "al-Kūlīra" and "Lockdown". The results of the study show that ESQ in the poem "al-Kūlīra" takes the form of the main virtues of honesty, empathy, and cooperation, while in the poem "Lockdown" ESQ is in the form of visionary, namely the ability to overcome the pandemic problem, as well as honesty, empathy, and cooperation. Abstrak Kondisi psikologis dari setiap negara yang mengalami wabah di setiap zaman pasti berbeda. Tulisan ini memaparkan kondisi psikologis pada puisi “al-Kūlīra” karya Nāzik al-Malāikah dan puisi “Lockdown” karya Simon Armitage. Kedua puisi ini berisi tentang situasi pandemi di dua negara yang berbeda. Puisi “al-Kūlīra” menceritakan wabah Kolera di Mesir, puisi “Lockdown” latar belakang penciptaanya adalah pandemi Korona. Teori psikologis yang digunakan adalah emotional spiritual quotient milik Ary Ginanjar. Kajian dimulai dengan menganalisis setiap dimensi psikologis dari kedua puisi tersebut untuk kemudian dibandingkan. Tujuan penelitian ini adalah mengetahui dan membandingkan kondisi psikologis berupa emotional spiritual quotient (ESQ) pada masyarakat yang terdampak pandemi corona dan kolera. Metode yang digunakan adalah deskriptif, komparatif, dan kualitatif dengan pendekatan psikologis. Data yang dipaparkan adalah setiap kata, frasa, klausa, dan kalimat yang mengandung unsur psikologis dari puisi “al-Kūlīra” dan “Lockdown”. Hasil penelitian menunjukkan bahwa ESQ pada puisi “al-Kūlīra” berupa budi utama kejujuran, empati dan kerja sama, sedangkan puisi “Lockdown” ESQ berupa visioner yaitu kemampuan untuk keluar dari masalah pandemi, kejujuran, empati, dan kerja sama.